PORTABLE CLOTHES WASHING MACHINE MODEL DESIGN ARDUINO BASED - Indryanto, Surya Puji; Hariono, Tholib (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The development of electronic technology provides great benefits for the world of electronics and for everyday life. Single chip computers, also called microcontrollers or microcomputers, also provide technology so that many human aids can be created. One of the tools to complete human tasks is washing clothes. Washing clothes is a routine task that humans do almost every day. It is true that automatic clothes washing machines have been created and many people are already using them, but in some cases, for example, people who travel or stay outside the home will find it difficult to carry or own a conventional clothes washing machine because it is large and takes up space to store. The aim of making this tool is to make it easier and simpler for people to use a clothes washing machine and to carry it everywhere. By using the Arduino system, the washing machine which originally used a module was replaced with an Arduino which is definitely simpler to use. Portability Easy to carry and use anywhere, including in dorms, small apartments, or while traveling. Efficiency Saves air and energy compared to general washing machines. Easy to use and operate. Suitable for small clothes: Ideal for washing small and delicate clothes, such as underwear, socks and towels.